The Effect of Personality Traits on the Performance of Students Enterprises - Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez; Noor Azlinna, Azizan; Elinda, Esa (Future Academy, 2019)
The study of the performance of student enterprises is relatively new, particularly in developing countries like Malaysia. Research into this topic is very important because several past studies have indicated that student enterprises have had an unimpressive performance record. Therefore, this study is designed to measure the effect of personality traits on the performance of student enterprises in Malaysian higher education institutions. This knowledge is important because the positive performance of student enterprises would encourage the government to produce job creators among university students. A cluster sampling technique was used to select 369 founders of student enterprises in Malaysian public higher education institutions, using an online survey and analysis using partial least squares structural equation modelling (PLS-SEM). Results found that innovativeness, locus of control and self-efficacy supported the performance and success of student enterprises, whereas the need for achievement and the propensity for risk taking did not influence the performance of student enterprises. This study has provided theoretical contributions to the literature and provides further insights into measuring the performance of student enterprises, particularly in Malaysia. This study could also assist policymakers and universities to reduce the number of unemployed graduates.